Long‐Term Outcomes in Patients With Connective Tissue Disease–Associated Pulmonary Arterial Hypertension in the Modern Treatment Era: Meta‐Analyses of Randomized, Controlled Trials and Observational Registries. Issue 5 (29th March 2021) - Khanna, Dinesh; Zhao, Carol; Saggar, Rajan; Mathai, Stephen C.; Chung, Lorinda; Coghlan, J. Gerry; Shah, Mehul; Hartney, John; McLaughlin, Vallerie
Abstract : Objective: Data on the magnitude of benefit of modern therapies for pulmonary arterial hypertension (PAH) in connective tissue disease (CTD)–associated PAH are limited. In this study, we performed meta‐analyses of randomized, controlled trials (RCTs) and registries to quantify the benefit of these modern therapies in patients with CTD‐PAH. Methods: The PubMed and Embase databases were searched for articles reporting data from RCTs or registries published between January 1, 2000 and November 25, 2019. Eligibility criteria included multicenter studies with ≥30 CTD‐PAH patients. For an RCT to be included, the trial had to evaluate an approved PAH therapy, and long‐term risks of clinical morbidity and mortality or 6‐minute walk distance had to be reported. For a registry to be included, survival rates had to be reported. Random‐effects models were used to pool the data. Results: Eleven RCTs (total of 4, 329 patients; 1, 267 with CTD‐PAH) and 19 registries (total of 9, 739 patients; 4, 008 with CTD‐PAH) were included. Investigational therapy resulted in a 36% reduction in the risk of clinical morbidity/mortality events both in the overall PAH population (hazard ratio [HR] 0.64, 95% confidence interval [95% CI] 0.54, 0.75; P < 0.001) and in CTD‐PAH patients (HR 0.64, 95% CI 0.51, 0.81; P < 0.001) as compared to control subjects. The survival rate was lower in CTD‐PAH patients compared to all PAH patients (survival rate 62%, 95% CI 57, 67% versus 72%, 95% CI 69, 75% at 3 years). The survival rate in CTD‐PAH patients treated primarily after 2010 was higher than that in CTD‐PAH patients treated before 2010 (survival rate 73%, 95% CI 62, 81% versus 65%, 95% CI 59, 71% at 3 years). Conclusion: Modern therapy provides a similar reduction in morbidity/mortality risk in patients with CTD‐PAH when compared to the PAH population overall. Risk of death is higher in CTD‐PAH patients than in those with PAH overall, but survival has improved in the last 10 years, which may be related to increased screening and/or new treatment approaches. Early detection of PAH in patients with CTD and up‐front intensive treatment are warranted.